Trade-off between India’s Trade Promotion and its Environmental Sustainability - Gore, Manasi; Annachhatre, Meenal (European Journal of Sustainable Development, 2019)
The concept of sustainable development involves three components namely economic, social and environmental. In a developing economy like that of India, the economic sustainability demands higher growth of key economic indicators such as National income, employment generation, production, consumption and even the foreign trade. The growth of foreign trade and that of the exports are very critical for the foreign exchange reserves essential to pay for the imports in India. Trade as an engine of the economic growth thus fulfils the essential implication for economic sustainability. But in achieving this growth, economy’s environmental sustainability is at stake. This is because, the top export products of India still comprise of petroleum products (18%) , agricultural products (12%), textiles and yarns together at 11 % and chemicals (10%). All these exports in their production have immensely contributed towards environmental pollution in one way or the other. Mining for gold, silver and diamonds resulted in water pollution, Green House Gas emission, and soil erosion. Petroleum refineries are a major source of hazardous and toxic air pollutants such as particulate matter (PM). Though India’s contribution to the total world trade is yet negligible, while promoting the major exports as mentioned above the natural resources are exploited too much and thus create a threat to India’s environmental sustainability. This paper therefore advocates the need for the Green products’ exports to make India’s growth story even environmentally sustainable. Keywords: Sustainable development, Green products, Exports, Imports, Environmental Pollution